Promoting Active Arabic Speaking Skills Through Talk or Dare Card Games - Febriyanti, Puput; Amrulloh, Muhammad Afif (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2024)
Learning Arabic speaking proficiency at MTs Darul Huffaz Pesawaran is still hampered by low student interest and limited learning media, so it is necessary to develop learning media, especially Talk or Dare cards. The study aimed to analyze student responses to the development of Talk or Dare card media as an interactive learning media for Arabic speaking proficiency and assess its feasibility for class VIII students of MTs Darul Huffaz Pesawaran. The type of research used is development research (Research and Development). Data sources were obtained through observation of the interaction and involvement of 25 students of class VIII in Arabic speaking skills in class. Furthermore, interviews with 8 students were conducted to discover the learning process's obstacles. Questionnaires were used to measure the feasibility of the media by two material experts and two media experts. The results showed a student response of 92% with a very positive category, while the feasibility according to the material expert was 92% and the media expert was 98% with a very feasible category. This research proves that Talk or Dare card media is effectively used to learn Arabic speaking proficiency.